Genotypic variation for salt tolerance in Moroccan barley landraces at seed germination - El Madidi, Said; El Baroudi, Brahim; Ban-Aameur, Fouzia (Plant Breeding and Seed Science, 2006)
Experiments were conducted to evaluate the genotypic variation for salt tolerance on seed germination for 24 genotypes (20 landraces and 4 breeding lines) of barley. The genotypeswere evaluated by several criteria, at 4 salt concentrations (0, 100 mM, 150 mM and 200 mM) and 4 seawater concentrations (0%, 20%, 30% and 40%). The results show a large variability within the genotypes for salt tolerance. Genotype × Treatment interaction is significant for root length. The estimates of broad-sense heritability calculated for percentage of germination (PG), percentage of emergence (PE) and radicle length (RL) were quite high for the salt treatment compared with those for the control treatment.Moderate to highBroad sens heritability estimateswere observed for the reduction percentage in both experiments. Discriminant analysis arranged the genotypes in two, clearly separate groups that differ in their tolerance to salinity stress.